School inclusion from the teaching perspective: reflections from legislative texts (Research, Society and Development, 2022)
The social inclusion of people with disabilities, and especially school inclusion, is a theme that has been gaining ground in national and international discussions, both in pedagogical political projects and in legislation. In this sense, this work seeks to understand how public policies support the educational practices of inclusion of teachers who work with students with disabilities. It is noticeable that Brazilian legislation ensures universal access to quality education, but it is still lacking when we think about the topic of inclusion. Analyzing in practice, we see that there is a lack of initial and continuing training for teachers, diverse human and material resources, adequate infrastructure in schools, as well as an inclusive mentality. The Federal Constitution, the Education Guidelines and Bases, the ECA and the Curriculum Guidelines for Special Education in Basic Education are examples of national legislation that address the right to education, access and permanence with quality in schools, however, in regard to children with disabilities, these laws diverge from the reality of regular schools, in view of the multiple attitudinal and concrete barriers that schools and students experience.